Datafication: the Flavor and Scent of Data - Botin, Lars (Yearbook of Medical Informatics, 2022)
This paper deals with data handling in health care on three distinct and different levels. The three levels can be classified in the following way: ethical level based on principles, political level based on negotiations and relations, and phenomenological level based on relation in between the physical and digital world. The paper takes an outset in a recent report, published in October 2021, from the Lancet and Financial Times Commission on governing health futures 2030 (ethical level), and a recent publication (2020) and exhibition at the Biennale of Architecture in Venice (2021) on Data Publics (political level), and finally makes an attempt to frame our being with digital technology on a philosophical and phenomenological level. It is the assumption that all these levels are needed the moment we try to appropriate and incorporate data in different arenas and worlds, might they be global, national, institutional, or/and individual.
Keywords: Ethics; politics; phenomenology; datafication; e-health; flesh